Stalin, der alte Schurke, der Teufel, der Zar, der Greis, und die Trauer Anna Seghers um seinen Tod - Vilar, M. Loreto (Revista de Filología Alemana, 2003)
It is not in the passionate articles that were published after the death of Stalin in March 1953, but in her second novel with a GDR subject, Das Vertrauen (Trust), that the communist author Anna Seghers dares to expose her own view of the Soviet dictator. Well aware of the difficulties –and political dangers– of offering a too realistic approach to the circumstances of his death, which include the false accusation and the unjust imprisonment of the doctors who attended him in his last days, the writer committed herself to a vision through the experiences of such characters as the old, unhappy worker Janausch, the much younger Thomas Helger, who slowly begins to question the omnipotence of the Party, his dogmatic girlfriend Lina Sachse, the honest Party secretary Richard Hagen, the old communist teacher Karl Waldstein, whose place in the new socialist structures no longer seems to matter, or even Woida and Berndt, who have fled to West Germany. The accurate description of their often clashing feelings about Stalin makes the author’s unwillingness to give her final word more evident, which in fact confirms the opinion she publicly chooses to silence. Seghers’ inability to praise the man who destroyed her quasireligious faith in the accomplishment of a truly just society speaks out nothing but her painful frustration about the realisation of the socialist utopia in the world